Konvergensi Media Periklanan dalam Konstelasi Perkembangan Teknologi Media - Widodo Agus Setianto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2008)
The recent development of information technology and commuitication with the presence of new media has affected human behaviors and habit especially in media consumption patterns. Efforts should be made by the conventional mass media, as advertising media, to be in line with the new media development. This article argues that the form of advertising media in the new media environment will be convergence media advertising.